Expression of a T39N mutant Rab32 protein arrests mitochondria movement within neurites of differentiated SH-SY5Y cells. (3rd July 2020) - Rybnicek, Jonas; Samtleben, Samira; Herrera-Cruz, Maria Sol; Simmen, Thomas
ABSTRACT: We have shown that multiple sclerosis (MS) and endoplasmic reticulum (ER) stress induce Rab32, an ER/mitochondria-localized small GTPase. High levels of both dominant-active (Q85L) or dominant-inactive (T39N) Rab32 are toxic to neurons. While Rab32Q85L interacts with its effector Drp1 to promote mitochondria fission, it is unclear how Rab32T39N could result as toxic to neurons. Given the perinuclear clustering of mitochondria observed upon transfection of inactive Rab32, we hypothesized Rab32T39N could stall mitochondria within neurites. The movement of mitochondria depends on kinesin-binding Miro proteins. High cytosolic [Ca 2+ ] is bound by an EF hand motif within Miro proteins, resulting in mitochondrial arrest. Consistent with increased cytosolic [Ca 2+ ], expression of Rab32T39N arrests mitochondria movement within neurites.